The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/jmrs.169
|View full text |Cite
|
Sign up to set email alerts
|

From the clinical to the managerial domain: the lived experience of role transition from radiographer to radiology manager in South‐East Queensland

Abstract: IntroductionThis study seeks to add to current literature a descriptive account of the lived experience of radiographers' transition to, and experiences of, management roles and identifies additional resources and support that are perceived as being beneficial for this transition.MethodsThis study employed a descriptive phenomenological stance. Using purposive sampling, six South‐East Queensland based private practice radiology managers, who had held their position for longer than 3 months, participated in aud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
4
5
0
Order By: Relevance
“…Qualitative analysis of this study's findings suggests that, in the hospital culture, nurses have more funding bodies for leadership development and more opportunities for leadership positions. These findings are consistent with previous research that indicates that leadership development has been a primary focus of the nursing profession for a longer time (Heard, 2014;Thompson & Henwood, 2016). This trend suggests that there are limited leadership opportunities for allied health care professions, though participants voiced that more leadership job postings have begun to surface in hospitals that are not strictly for those in the nursing profession.…”
Section: Environmentsupporting
confidence: 88%
See 3 more Smart Citations
“…Qualitative analysis of this study's findings suggests that, in the hospital culture, nurses have more funding bodies for leadership development and more opportunities for leadership positions. These findings are consistent with previous research that indicates that leadership development has been a primary focus of the nursing profession for a longer time (Heard, 2014;Thompson & Henwood, 2016). This trend suggests that there are limited leadership opportunities for allied health care professions, though participants voiced that more leadership job postings have begun to surface in hospitals that are not strictly for those in the nursing profession.…”
Section: Environmentsupporting
confidence: 88%
“…Thus, it is suggested that by developing and maintaining relationships in and beyond one's own organization, occupational therapists can create leadership opportunities and positive connections that may further assist their career development. Consistent with previous literature, the findings of this study suggest that occupational therapists are more likely to pursue leadership roles if they are intrinsically motivated through their desire to influence the profession or their desire for career advancement (Heard, 2014;Thompson & Henwood, 2016).…”
Section: Personsupporting
confidence: 87%
See 2 more Smart Citations
“…Newly qualified radiographers require formalised institutional direction and support, and at the very basic level, a job orientation, clear job descriptions, and mentorship should be standard departmental policy. 14,15…”
Section: Collegial Environmentmentioning
confidence: 99%